Biochemical Characterization of the ctr Mutants of Escherichia coli - Morse, Helvise G. (1971)
A test procedure based on complementation in mixed extracts is described for the assay of heat-stable protein and enzyme I of the phosphoenolpyruvate-dependent phosphotransferase system. The test was used to assay a collection of pleiotropic carbohydrate mutants of Escherichia coli (ctr mutants) and revertants of these mutants. All mutants were found to lack enzyme I of the phosphoenolpyruvate-dependent transferase system. Revertants of these mutants to complete wild phenotype regained enzyme I-forming ability. Reversion to partial wild type was not accompanied by restoration of enzyme I-forming ability.